Rhinovirus Infection Is Associated With Airway Epithelial Cell Necrosis and Inflammation via Interleukin-1 in Young Children With Cystic Fibrosis - Montgomery, Samuel T.; Frey, Dario L.; Mall, Marcus A.; Stick, Stephen M.; Kicic, Anthony; , AREST CF (Frontiers in Immunology, 2020)
Introduction: The responses of cystic fibrosis (CF) airway epithelial cells (AEC) to rhinovirus (RV) infection are likely to contribute to early pathobiology of lung disease with increased neutrophilic inflammation and lower apoptosis reported. Necrosis of AEC resulting in airway inflammation driven by IL-1 signalling is a characteristic finding in CF detectable in airways of young children. Being the most common early-life infection, RV-induced epithelial necrosis may contribute to early neutrophilic inflammation in CF via IL-1 signalling. As little is known about IL-1 and biology of CF lung disease, this study assessed cellular and pro-inflammatory responses of CF and non-CF AEC following RV infection, with the hypothesis that RV infection drives epithelial necrosis and IL-1 driven inflammation. Methods: Primary AEC obtained from children with (n=6) and without CF (n=6) were infected with RV (MOI 3) for 24 hours and viable, necrotic and apoptotic events quantified via flow cytometry using a seven-step gating strategy (% total events). IL-1α, IL-1β, IL-1Ra, IL-8, CXCL10, CCL5, IFN-β, IL-28A, IL-28B, and IL-29 were also measured in cell culture supernatants (pg/mL). Results: RV infection reduced viable events in non-CF AEC (p<0.05), increased necrotic events in non-CF and CF AEC (p<0.05) and increased apoptotic events in non-CF AEC (p<0.05). Infection induced IL-1α and IL-1β production in both phenotypes (p<0.05) but only correlated with necrosis (IL-1α: r=0.80; IL-1β: r=0.77; p<0.0001) in CF AEC. RV infection also increased IL-1Ra in non-CF and CF AEC (p<0.05), although significantly more in non-CF AEC (p<0.05). Finally, infection stimulated IL-8 production in non-CF and CF AEC (p<0.05) and correlated with IL-1α (r=0.63 & r=0.74 respectively; p<0.0001). Conclusions: This study found RV infection drives necrotic cell death in CF AEC. Furthermore, the induced IL-1 strongly correlated with necrotic cell death in these cells. As IL-1R signalling drives airway neutrophilia and mucin production, these observations suggest RV infection early in life may exacerbate inflammation and mucin accumulation driving early CF lung disease. Since IL-1R can be targeted therapeutically with IL-1Ra, these data suggest a new anti-inflammatory therapeutic approach targeting downstream effects of IL-1R signalling to mitigate viral-induced, muco-inflammatory triggers of early lung disease.